IVA no Brasil e as repercussões de sua adoção frente aos municípios - Aragão, Jackcyane Vitória Maria de Melo (2020)
This monograph will bring to light an explanatory study on a concrete topic, relatively new and little studied. In this paper the discussion about the repercussions of the possible adoption of a system of tax on the additional value, with the tax reform, in the Brazilian municipal entities will be approached. The Tax Reform is justified on the grounds that it is outdated and a change is necessary, and the proposal is the adoption of the VAT model. In the present work, a rescue and contextualization will be made about what the Value Added Tax is, as well as its repercussions in the economic blocs of the European and South American community. To this end, it will be necessary to address the reasons for the need for a reform in the national tax structure and the proposals for amendments to the constitution launched will be analyzed. Finally, the burden of these proposals will be analyzed before Brazilian municipal entities, and the solutions found by the National Confederation of Municipalities will be explained. It is a theoretical and documentary research, made from the analysis of the legislation, doctrine and domestic jurisprudence. It will also use comparative law for a better understanding of the topic. The present work aims to propose ways to change the national tax system without harming municipal entities, essential entities for the heart of the country.